Studi Korelasional Kualitas Komunikasi dengan Kualitas Hubungan Pacaran Jarak Jauh - Ferina Reza Megantara (Jurnal Riset Psikologi, 2025)
Abstract. This study aims to examine the relationship between communication quality and the quality of long-distance dating relationships (LDDR). This phenomenon has become increasingly relevant with the advancement of technology that allows for intensive long-distance communication. The research employs a quantitative approach using a survey questionnaire involving 388 respondents in Bandung. The results of Spearman's correlation analysis indicate a significant positive relationship between communication quality and relationship quality (r = 0.742). This study also emphasizes the importance of communication quality in maintaining long-distance relationships, providing theoretical and practical insights for couples in similar situations. Abstrak. Penelitian ini bertujuan untuk mengkaji hubungan antara kualitas komunikasi dengan kualitas hubungan pacaran jarak jauh. Fenomena ini menjadi semakin relevan dengan kemajuan teknologi yang memungkinkan komunikasi jarak jauh secara intensif. Penelitian menggunakan pendekatan kuantitatif dengan metode survei kuesioner yang melibatkan 388 responden di Kota Bandung. Hasil analisis korelasi Spearman menunjukkan hubungan positif yang signifikan antara kualitas komunikasi dan kualitas hubungan (r = 0,742). Penelitian ini juga menegaskan pentingnya kualitas komunikasi dalam menjaga hubungan jarak jauh, memberikan wawasan teoretis dan praktis bagi pasangan dalam situasi serupa.